2017
DOI: 10.2147/ijn.s144305
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of ginsenoside compound K using TPGS/PEG-PCL mixed micelles for effective treatment of lung cancer

Abstract: Ginsenoside compound K (CK) is one of the effective ingredients in antitumor composition of ginsenoside. However, the poor water solubility and significant efflux have limited the widespread clinical use of CK. In this study, preparation of novel CK-loaded d -alpha-tocopheryl polyethylene glycol 1,000 succinate/poly(ethylene glycol)-poly(ε-caprolactone) mixed micelles (CK-M) is discussed to solve the above problems. Particle size, zeta potential, and morphology were characterized using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Ginsenoside CK, a major member of the originally reported ginseng diol saponin, has been a topic of research in the fields of anti-inflammatory and antitumor effects. Recent studies have revealed that ginsenoside CK has anti-inflammatory, antioxidative, and neuroprotective effects (13)(14)(15)(16), and of particular interest are its antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside CK, a major member of the originally reported ginseng diol saponin, has been a topic of research in the fields of anti-inflammatory and antitumor effects. Recent studies have revealed that ginsenoside CK has anti-inflammatory, antioxidative, and neuroprotective effects (13)(14)(15)(16), and of particular interest are its antitumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nanocrystals for PPD formulation improved oral bioavailability and brain delivery [15]. The use of the metabolism inhibitor piperine [20] in the formulation of PPD and the use of P-gp inhibitor, α-Tocopheryl polyethylene glycol 1000 succinate (TPGS) [21], in the formulation of PPD and compound K enhanced oral absorption and anticancer efficacy of these PPD and compound K [22,23]. These approaches may provide a strategy for developing formulations for compound K and PPD by modulating their pharmacokinetic features.…”
Section: Discussionmentioning
confidence: 99%
“…The critical micelle concentration (CMC) of TPGS-Solutol was determined by a pyrene fluorescence method. 31 The characterization of the PHTSm including particle size distribution, polydispersity index (PDI), and zeta potential were measured by a Zetasizer (Nano ZS90; Malvern Panalytical, Malvern, UK). Its morphology was observed through a transmission electron microscope (TEM) and atomic force microscopy (AFM).…”
Section: Characterizationmentioning
confidence: 99%